Teaching Amidst the Pandemic: Exploring the Perceptions and Experiences of Teachers in Remote Rural Municipalities in the Philippines - Legarde, Michael Angelo A.; Sumandal, Arman H. (Future Science / FSH-PH Publications, 2022)
The world has been shaken by the advent of the COVID-19 pandemic, which has resulted in a dramatic loss of human life and poses an unprecedented challenge to almost all aspects of life, and the Philippines has not been an exception to these challenges. As a result, this deadly situation has flipped the offline teaching process and paved the way towards online-based teaching. This study was conducted to determine the perceptions and experiences of teachers in the remote areas towards online teaching. This study employed a cross-sectional explanatory research design and the analyses reveal that respondents with